Dialectal Features Of The Speech Of Kazakhs In Uzbekistan And Their Socio-Linguistic Factors (Texas Journal of Philology, Culture and History, 2026)
This scientific article highlights the role of language as a complex system that expresses national identity, social consciousness, and cultural values. It also examines the significance of dialectology in studying the territorial variability of language, the dialectal system of the Kazakh language, and its historical and areal development features. The phonetic, lexical, and morphological characteristics of Kazakh dialects spoken in Uzbekistan, particularly the Tashkent Kazakh dialect, are analyzed from the perspective of contact linguistics. The article also scientifically discusses linguistic relations between the Uzbek and Kazakh languages, as well as processes of interference and convergence. The results of the research demonstrate that studying territorial linguistic variation, preserving dialects, and deepening the understanding of Turkic interlingual relations is of great importance